Tinjauan Kompetensi Profesional Guru Bersertifikat Pendidik Terhadap Efektivitas Pembelajaran - Jumrawati, Jumrawati; Lina, Karoluslina (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2025)
Abstract: This study investigates the implementation of certified teachers’ professional competencies and their influence on the quality and effectiveness of learning at SMPN 12 Poleang Barat. The research particularly focuses on five key domains: subject matter mastery, development of contextually relevant instructional materials, integration of technology in pedagogical practices, continuous assessment, and sustained professional engagement through reflective practice and scholarly participation. Employing a qualitative approach, data were collected through in-depth interviews, classroom observations, and document analysis. The findings reveal a range of variability in the application of professional competencies among certified teachers. While certain educators demonstrated the ability to transform their competencies into structured, adaptive, and participatory learning environments, others exhibited inconsistencies, particularly in the use of instructional technology and reflective strategies. These disparities directly impacted instructional effectiveness, evidenced by variations in student engagement, learning achievement, and instructional responsiveness. The study concludes that teacher certification alone is insufficient to ensure professional excellence unless accompanied by consistent competency application and supported through ongoing, structured post-certification professional development. Accordingly, the study advocates for a reinforcement of reflective mentoring systems and the contextualization of continuous learning frameworks to optimize pedagogical outcomes.Key Words: Professional Competence, Teacher Certification, Learning EffectivenessAbstrak: Penelitian ini bertujuan untuk mengkaji implementasi kompetensi profesional guru bersertifikat pendidik dan dampaknya terhadap kualitas serta efektivitas pembelajaran di SMPN 12 Poleang Barat. Fokus kajian diarahkan pada penguasaan materi ajar, pengembangan bahan ajar yang kontekstual, pemanfaatan teknologi dalam proses pembelajaran, pelaksanaan evaluasi yang berkelanjutan, serta keterlibatan guru dalam pengembangan keprofesian melalui refleksi dan kegiatan ilmiah. Pendekatan kualitatif digunakan dengan teknik pengumpulan data berupa wawancara mendalam, observasi kelas, dan studi dokumen. Hasil temuan menunjukkan bahwa meskipun guru telah memperoleh pengakuan formal melalui sertifikasi pendidik, terdapat variasi dalam implementasi kompetensi profesional di lapangan. Guru yang mampu mengintegrasikan kompetensinya secara optimal terbukti mampu menciptakan proses pembelajaran yang lebih terstruktur, adaptif, dan partisipatif, sehingga berdampak positif pada efektivitas pembelajaran, seperti peningkatan keterlibatan siswa, pencapaian tujuan pembelajaran, dan pemanfaatan strategi instruksional yang lebih kontekstual. Temuan ini menegaskan bahwa efektivitas pembelajaran bukan hanya ditentukan oleh keberadaan sertifikasi semata, tetapi juga oleh sejauh mana kompetensi profesional diterapkan secara konsisten dalam praktik pembelajaran. Penelitian ini merekomendasikan penguatan pembinaan pasca-sertifikasi yang berfokus pada pendampingan reflektif dan pengembangan kompetensi yang berkelanjutan.Kata Kunci: Kompetensi Profesional, Sertifikasi Guru, Efektivitas Pembelajaran.